Dynamic Pituitary-Adrenal Interactions in Response to Cardiac Surgery*. Issue 4 (April 2015) - Gibbison, Ben; Spiga, Francesca; Walker, Jamie J.; Russell, Georgina M.; Stevenson, Kirsty; Kershaw, Yvonne; Zhao, Zidong; Henley, David; Angelini, Gianni D.; Lightman, Stafford L.
Abstract : Objectives: To characterize the dynamics of the pituitary-adrenal interaction during the course of coronary artery bypass grafting both on and off pump. Since our data pointed to a major change in adrenal responsiveness to adrenocorticotropic hormone, we used a reverse translation approach to investigate the molecular mechanisms underlying this change in a rat model of critical illness. Design: Clinical studies: Prospective observational study. Animal studies: Controlled experimental study. Setting: Clinical studies: Cardiac surgery operating rooms and critical care units. Animal studies: University research laboratory. Subjects: Clinical studies: Twenty, male patients. Animal studies: Adult, male Sprague-Dawley rats. Interventions: Clinical studies: Coronary artery bypass graft—both on and off pump. Animal studies: Injection of either lipopolysaccharide or saline (controls) via a jugular vein cannula. Measurements and Main Results: Clinical studies: Blood samples were taken for 24 hours from placement of the first venous access. Cortisol and adrenocorticotropic hormone were measured every 10 and 60 minutes, respectively, and corticosteroid-binding globulin was measured at the beginning and end of the 24-hour period and at the end of operation. There was an initial rise in both levels of adrenocorticotropic hormone and cortisol to supranormal values at around the end of surgery. Adrenocorticotropic hormone levels then returned toward preoperative values. Ultradian pulsatility of both adrenocorticotropic hormone and cortisol was maintained throughout the perioperative period in all individuals. The sensitivity of the adrenal gland to adrenocorticotropic hormone increased markedly at around 8 hours after surgery maintaining very high levels of cortisol in the face of "basal" levels of adrenocorticotropic hormone. This sensitivity began to return toward preoperative values at the end of the 24-hour sampling period. Animal studies: Adult, male Sprague-Dawley rats were given either lipopolysaccharide or sterile saline via a jugular vein cannula. Hourly blood samples were subsequently collected for adrenocorticotropic hormone and corticosterone measurement. Rats were killed 6 hours after the injection, and the adrenal glands were collected for measurement of steroidogenic acute regulatory protein, steroidogenic factor 1, and dosage-sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1 messenger RNAs and protein using real-time quantitative polymerase chain reaction and Western immunoblotting, respectively. Adrenal levels of the adrenocorticotropic hormone receptor (melanocortin type 2 receptor) messenger RNA and its accessory protein (melanocortin type 2 receptor accessory protein) were also measured by real-time quantitative polymerase chain reaction. In response to lipopolysaccharide, rats showed a pattern of adrenocorticotropic hormone and corticosterone that was similar to patients undergoing coronary artery bypass grafting. We were also able to demonstrate increased intra-adrenal corticosterone levels and an increase in steroidogenic acute regulatory protein, steroidogenic factor 1, and melanocortin type 2 receptor accessory protein messenger RNAs and steroidogenic acute regulatory protein, and a reduction in dosage-sensitive sex reversal, adrenal hypoplasia critical region, on chromosome X, gene 1 and melanocortin type 2 receptor messenger RNAs, 6 hours after lipopolysaccharide injection. Conclusions: Severe inflammatory stimuli activate the hypothalamic-pituitary-adrenal axis resulting in increased steroidogenic activity in the adrenal cortex and an elevation of cortisol levels in the blood. Following coronary artery bypass grafting, there is a massive increase in both adrenocorticotropic hormone and cortisol secretion. Despite a subsequent fall of adrenocorticotropic hormone to basal levels, cortisol remains elevated and coordinated adrenocorticotropic hormone-cortisol pulsatility is maintained. This suggested that there is an increase in adrenal sensitivity to adrenocorticotropic hormone, which we confirmed in our animal model of immune activation of the hypothalamic-pituitary-adrenal axis. Using this model, we were able to show that this increased adrenal sensitivity results from changes in the regulation of both stimulatory and inhibitory intra-adrenal signaling pathways. Increased understanding of the dynamics of normal hypothalamic-pituitary-adrenal responses to major surgery will provide us with a more rational approach to glucocorticoid therapy in critically ill patients.